Development of a 31P magnetic resonance spectroscopy technique to quantify NADH and NAD+ at 3 T - Julian Mevenkamp; Yvonne M. H. Bruls; Rodrigo Mancilla; Lotte Grevendonk; Joachim E. Wildberger; Kim Brouwers; Matthijs K. C. Hesselink; Patrick Schrauwen; Joris Hoeks; Riekelt H. Houtkooper; Mijke Buitinga; Robin A. de Graaf; et al. (Nature Communications, 2024)
Abstract NADH and NAD+ act as electron donors and acceptors and NAD+ was shown to stimulate mitochondrial biogenesis and metabolic health. We here develop a non-invasive Phosphorous Magnetic Resonance Spectroscopy (31P-MRS) method to quantify these metabolites in human skeletal muscle on a clinical 3 T MRI scanner. This new MR-sequence enables NADH and NAD+ quantification by suppressing α-ATP signal, normally overlapping with NADH and NAD+. The sequence is based on a double spin echo in combination with a modified z-Filter achieving strong α-ATP suppression with little effect on NAD+ and NADH. Here we test and validate it in phantoms and in humans by measuring reproducibility and detecting a physiological decrease in NAD+ and increase in NADH induced by ischemia. Furthermore, the 31P-MRS outcomes are compared to analysis in biopsies. Additionally, we show higher NAD+ and lower NADH content in physically active older adults compared to sedentary individuals, reflecting increased metabolic health.